Modify PRESENT Algorithm by New technique and key Generator by External unit - Ahmed Abdullah Khalil; Awny Muhammed Kaftan; Maytham Mustafa Hammoud (Tikrit Journal of Pure Science, 2023)
Recently, the widespread use of devices in the field of electronics has caused people to worry about safety. Using traditional cryptographic algorithms to build a complete cryptographic environment for embedded applications or the Internet of Things (IoT) will not be possible due to space, power, and speed limitations. The focus is on lightweight encryption to overcome these problems. In this paper, we have developed the (PRESENT) algorithm, which is among the lightweight algorithms that are used in the IOT and that keeps pace with the requirements of communication speed at the present time. We also used a physical part with the developed algorithm (an external unit that is a USB and using it as a fingerprint for the system) to generate the key while ensuring that the system does not work until after the external unit is connected to the calculator to provide more security for the system from breaches. The developed algorithm achieved a high speed of execution faster than the original algorithm and passed standard tests for various files (text, image, audio, video). In addition to increasing the degree of complexity than the original algorithm.